Assessment of the influence of pole carriage on sprint kinematics: A case study of novice athletes - Frere, J.; Chollet, D.; Tourny-Chollet, C. (International Journal of Sports Science and Engineering, 2009)
The purpose of this study was to determine the influence of pole carrying on the biomechanics of the run-up in the pole vault. Eight novice male pole vaulters participated and performed six 30-m sprints, three with and three without a pole. A tripod-mounted digital video camera was horizontally panned to follow the athletes from left to right and electronic timing cells recorded the sprint times. The experimental set-up recorded the average velocities and the times of the stance and swing phases; it also determined the sagittal plane angles of the hip, knee and ankle joints during a cycle. The results indicated that the average velocities during the runs were significantly lower with pole than without (P < 0.05). The runs with pole were characterized by significantly less flexion of the hip and knee joints at the instant of maximal hip flexion during the swing phase. Consequently, an anterior imbalance was created by running with a pole whose length was much greater than the athletes` height. This tended to increase the braking phase and decrease the stride length, causing a `slight precipitation` by the athletes` anticipation of the foot touch-down.